Re-visiting to Raúl Prebisch and the role of the CEPAL in the field of the Latin-American social sciences - Gabay, Ruth Eliana (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2008)
This paper alludes to the role played by Raúl Prebisch and the CEPAL in the process of pro- duction and institutionalization of a certain social and critical knowledge in the 50’s in Latin America. From a bourdian perspective our aim is to go beyond biographical constructions that have been written about Prebisch's work and settle them down to the ideas developed by CEPAL. Because of that, we will try to analyze, on one hand, Prebisch’s theoretical and strate- gic position in the field of social sciences at that time and to explain, on the other hand, CEPAL’s blurred image due to the crisis of the substitute industrialization model, Prebisch's movement to the UNCTAD and the Dependent Economy Model debate in Latin America academy.